The Impact of Antiviral Therapy and the Influence of Metabolic Cofactors on the Outcome of Chronic HCV Infection - Marcello Persico; Savino Bruno; Andrea Costantino; Marta Mazza; Piero Luigi Almasio (International Journal of Hepatology)
Natural history of HCV related chronic hepatitis is influenced and modified by many factors: virus features, coinfections and host characteristics. In particular, a peculiar genetic background of the host by conditioning the occurrence of intracellular metabolic derangements (i.e., insulin resistance) might contribute to accelerate the rate of progression to cirrhosis and eventually the occurrence of hepatocellular carcinoma (HCC) and death. Likely, direct interplays between virus genotype and host genetic background might be hypothesized at this level. Morbidity and mortality in cirrhosis is primarily associated with complications of liver cirrhosis (ascites, hepatic encephalopathy, jaundice, and gastroesophageal bleeding) and HCC occurrence. Therefore the main goal of therapy is to clear viral infection and decrease liver necro-inflammation that directly relates to development of cirrhosis and HCC. Among patients treated with Interferon-based therapy, those with sustained viral response showed a significant reduction of progression to cirrhosis and development of HCC. However, a residual risk of hepatocellular carcinoma still remains indicating the need for careful follow-up using ultrasonography every six months in cirrhotic patients, even in those showing persistently normal ALT and undetectable HCV RNA levels after antiviral therapy.